Green Synthesis of Silver Nanoparticles Using Juniperus procera Extract: Their Characterization, and Biological Activity - Merajuddin Khan; Ponmurugan Karuppiah; Hamad Z. Alkhathlan; Mufsir Kuniyil; Mujeeb Khan; Syed Farooq Adil; Mohammed Rafi Shaik (Crystals, 2022)
Plant extract-based green synthesis of metal nanoparticles (NPs) has become a popular approach in the field of nanotechnology. In this present investigation, silver nanoparticles were prepared by an efficient and facile approach using Juniperus procera extract as a bioreducing and stabilizing agent. The as-synthesized silver nanoparticles (JP-AgNPs) were characterized by several characterization techniques such as UV–Vis, XRD, FT-IR, HR-TEM, and EDX analysis. The XRD analysis evidently confirms that the as-synthesized Ag nanoparticles (NPs) from Juniperus procera plant extract (JP-AgNPs) are crystalline in nature. FT-IR analysis confirms that the plant extract plays a dual role as a bioreducing and capping agent, while HR-TEM revealed the spherical morphology of as-synthesized JP-AgNPs with the size of ~23 nm. Furthermore, the synthesized JP-AgNPs were evaluated for antibacterial properties against several bacterial and fungal strains such as Staphylococcus aureus (ATCC 12228), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Proteus mirabilis (ATCC 4753), Cryptococcus neoformans (ATCC 16620), and Candida albicans (ATCC 885-653). The JP-AgNPs displayed an efficient mean zone of inhibition (MZI) at 50.00 µL for bacterial associated with fungal pathogens than the plant extract. Mainly, MZI values against microbial pathogens were as follows; E. coli (17.17 ± 0.72 mm), P. mirabilis (14.80 ± 0.17 mm), and C. albicans (14.30 ± 0.60 mm), whereas JP-AgNPs showed moderate activity against P. aeruginosa (11.50 ± 0.29 mm) and C. neoformans (9.83 ± 0.44 mm). Notably, the tested JP-AgNPs have displayed almost similar antimicrobial activities with that of standard antimicrobial drugs, such as streptomycin and nystatin. The enhanced antimicrobial activity of JP-AgNPs can be ascribed to the quality of resultant NPs including, uniform size, shape, and aqueous colloidal stability of nanoparticles.